A Comparison Study of Depression and Quality of Life in Turkish Mothers of Children with down Syndrome, Cerebral Palsy, and Autism Spectrum Disorder. Issue 1 (February 2013) - Tekinarslan, Ilknur Cifci
This study aimed to compare the quality of life and depression levels in Turkish mothers of children with Down syndrome, cerebral palsy, and Autism Spectrum Disorder (ASD). An additional purpose is to identify whether the depression and quality of life levels of the mothers differ significantly based on demographic variables. Two hundred fifty-two mothers participated in the study. The World Health Organization's Quality of Life-BREF (WHOQOL-BREF–TR) assessment instrument was used to determine the mothers' quality of life and the Beck Depression Inventory (BDI) to characterize their depression. Mothers of children with cerebral palsy had significantly lower quality of life scores on the environment and national environment domains of the WHOQOL-BREF–TR than those of children with Down syndrome. No significant difference was observed in the depression of mothers. With increasing education and income, quality of life of the mothers increased whereas depression decreased. Moreover, depression increased and quality of life decreased in older mothers. Furthermore, the findings indicated significant negative correlations between mothers' depression and quality of life scores on all domains of the WHOQOL-BREF–TR.